Statistical properties of rates of return of the companies listed on the Warsaw Stock Exchange in the period of 2005-2015 - Dębski, Wiesław; Feder-Sempach, Ewa; Wójcik, Szymon (Własności statystyczne stóp zwrotu spółek notowanych na GPW w Warszawie w latach 2005-2015, 2017)
The rates of return of listed companies are subject to numerous studies, particularly those listed on the stock exchange. Information about rates of return are useful primarily for investors choosing an investment, estimating its risk and profitability of the investment made. Among these studies, many of them are devoted to the examination of the statistical properties of the rates of return. The aim of the article is to examine the statistical properties of the monthly rates of return of companies listed on the Warsaw Stock Exchange in the period of 2005-2015. Such parameters as mean value, standard deviation, semi-standard deviation, skewness and kurtosis will be studied, and whether the rates of return have a normal distribution. These properties will be investigated for the whole market and broken down into bull and bear market conditions
Ekonometria = Econometrics, 2017, Nr 3 (57), s. 88-100
Keywords: rates of return; shares listed on stock exchange; statistical properties; bull and bear market; stopy zwrotu; akcje notowane na giełdzie; własności statystyczne; rynekbyka i niedźwiedzia